2011
DOI: 10.1158/0008-5472.can-10-4645
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Replacement Therapy for miR-145 and miR-33a Is Efficacious in a Model of Colon Carcinoma

Abstract: MicroRNAs (miRNA) aberrantly expressed in tumors may offer novel therapeutic approaches to treatment. miR-145 is downregulated in various cancers including colon carcinoma in which in vitro studies have established proapoptotic and antiproliferative roles. miR-33a was connected recently to cancer through its capacity to downregulate the oncogenic kinase Pim-1. To date, miRNA replacement therapy has been hampered by the lack of robust nonviral delivery methods for in vivo administration. Here we report a method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
231
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(240 citation statements)
references
References 42 publications
6
231
0
1
Order By: Relevance
“…Recently, a number of miRNAs were found to be aberrantly expressed in cancer cells, and to play a role in regulating cancer progression (Huang and He, 2011). An intronic miRNA located within the gene encoding sterol-regulatory element-binding factor-2 (SREBF-2), miR-33, regulates cholesterol metabolism in concert with SREBPs, contributing to tumor growth Ibrahim et al, 2011), suggesting a therapeutic potential for miRNA modulation.…”
Section: Cancer-related Regulators Of Cholesterol Metabolismmentioning
confidence: 99%
“…Recently, a number of miRNAs were found to be aberrantly expressed in cancer cells, and to play a role in regulating cancer progression (Huang and He, 2011). An intronic miRNA located within the gene encoding sterol-regulatory element-binding factor-2 (SREBF-2), miR-33, regulates cholesterol metabolism in concert with SREBPs, contributing to tumor growth Ibrahim et al, 2011), suggesting a therapeutic potential for miRNA modulation.…”
Section: Cancer-related Regulators Of Cholesterol Metabolismmentioning
confidence: 99%
“…23,24 Moreover, it was shown that PEI can also efficiently deliver siRNA complexed with it to tumors in mice after systemic administration. 25, 26 We therefore chose to employ PEI as a carrier for RRM1-specific siRNA in this study.…”
Section: More Importantly a Higher Levelmentioning
confidence: 99%
“…3 Emerging evidence has shown that miRNAs are involved in cancer initiation and progression. 4 MiR-145 has been reported as an important tumor suppressor gene in ovarian carcinoma, 5,6,7 malignant pleural mesothelioma, 8 breast cancer, 9 pancreatic cancer, 10,11 liposarcoma, 12 colorectal cancer, 13,14,15,16 neuroblastoma, 17 breast cancer, 18,19,20,21 esophageal cancer, 22 bladder cancer, 23,24 urothelial cancer, 25 prostate cancer, 26,27 gastric cancer, 28 and head and neck cancer, 29 and other types. MiR-145 was also implicated in the progression of NSCLC; 30,31,32 however, its exact mechanism is not well established.…”
Section: Introductionmentioning
confidence: 99%